(untitled) (LEARNing Landscapes, 2021)
In this case study, we explore ways to prepare preservice teachers to translate theory into practice and make science curriculum accessible through familial curriculum. Using her “Family Science Lesson Planning” assignment sequence, Sumer taught preservice teachers the theory of transformative curriculum making (Seiki, 2016), and guided them to recognize, articulate, and translate their own familial curriculum into science lessons. As a result, the three participant preservice teachers’ own histories and familial knowledge were repositioned and valued alongside science. Our findings show how to use science curriculum and instruction to border cross between home and school, thereby making science more accessible.